2013
DOI: 10.1002/isaf.1337
|View full text |Cite
|
Sign up to set email alerts
|

Incase: Simulating Experience to Accelerate Expertise Development by Knowledge Workers

Abstract: SUMMARY INCASE, a web-based electronic learning (e-learning) environment, has been built to enable rapid expertise development in novice-level professional knowledge workers. This paper describes the theoretical underpinnings (constructivist epistemology) behind INCASE and uses a design science methodology to describe its design, construction, instantiation, and validation. The INCASE system addresses a fundamental problem in knowledge worker domains where experience is a necessary component of expertise devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Testing of the Theory of Technology Dominance has also been at the core of what is recognised as the INSOLVE project (Arnold et al ., , ,b, , , , ). Insolvency professionals were targeted to get into a high‐risk environment with highly specialised professionals.…”
Section: Auditing and Assurancementioning
confidence: 99%
“…Testing of the Theory of Technology Dominance has also been at the core of what is recognised as the INSOLVE project (Arnold et al ., , ,b, , , , ). Insolvency professionals were targeted to get into a high‐risk environment with highly specialised professionals.…”
Section: Auditing and Assurancementioning
confidence: 99%
“…Researchers have been studying the impact of AI and its predecessor technologies on work processes and employee wellbeing since the late 1980s. A series of studies focused on the negative effects of knowledge support systems and artificial intelligence on workers’ wellbeing, and their learning, growth, and development (Arnold & Sutton, 1998; Arnold et al, 2004; 2006; 2013). Sutton and Arnold, 2018 evoked Braverman’s (1974) work arguing that the implementation of scientific management and consolidation of labor in large, production line-based facilities results in deconstructing of high skill work into smaller pieces that can be easily performed by machines or low-skilled workers.…”
Section: Expertise and Expertise Developmentmentioning
confidence: 99%
“…Thus, the need for high-skilled (and more expensive) workers is decreasing; workers lack pride of artisanship, work meaning, and are forced to accept lower-paid and more precarious jobs. While Braverman was mostly concerned with manual and crafts-based labor, Arnold, Sutton, and their colleagues focused on the impact of automation on the skilled knowledge work of accountants and auditors (e.g., Arnold et al, 2006; Arnold et al, 2013). They argued that, while on the surface it may seem that with the assistance of machines knowledge workers can solve problems that are more complex and operate at higher levels of skill, in reality, they lack opportunities to learn and develop their expertise since machines take over large chunks of work.…”
Section: Expertise and Expertise Developmentmentioning
confidence: 99%
“…Patterson et al (2013) demonstrated that in using CTA based curriculum, it is possible to accelerate on-the-job performance. Some researchers have used scenario-based learning with real-world cases to train complex skills (Arnold, Collier, & Vincent, 2013). Doane, Alderton, Sohn, & Pellegrino (1996)demonstrated that difficult or tough cases could accelerate the proficiency of individuals.…”
Section: Page4mentioning
confidence: 99%